Genetic Diversity of Spotted Large White, Large White and Pietrain Using Microsatellite Analysis - Sompoch Tabchareon; Srisuwan Chomchai; Neramit Sookmanee; Wanee Chaiwatanasin; Somwong Trakulrung (Agriculture and Natural Resources, 2002)
Thirty-six microsatellite loci were analyzed in 30 random individuals to characterize the genetic variability of Spotted Large White (SLW), Large White (LW) and Pietrain(PT). Mean numbers of allele per locus, mean numbers of shared allele per locus and average gene diversity per locus were 5.39, 2.14 and 0.6646, respectively. Polymorphism information content (PIC), observed and expected heterozygosity of SLW (0.5138, 0.5667 and 0.6344, respectively) were lower than the values in LW (0.5685, 0.5706 and 0.6943, respectively) and PT (0.5236, 0.4806 and 0.6439). Base on Nei’ standard genetic distance, there was a great genetic differentiation between SLW and the other two breeds. Similarly, individual clustering based on the proportion of shared alleles showed that SLW individuals formed a single cluster separated from the other two pig breeds.